HUBUNGAN JUMLAH KOMPLIKASI DIABETES MELITUS DENGAN STATUS FUNGSIONAL PADA PASIEN DIABETES MELITUS DI POLIKLINIK PENYAKIT DALAM RSUP SANGLAH DENPASAR, PROVINSI BALI - Gusti Ayu Krisma Yuntari (Coping: Community of Publishing in Nursing, 2013)
Abstract. Diabetes mellitus is metabolic diseases characteristed by hyperglycemia that occurs by abnormalities of insulin secretion, insulin action or both. Complications of diabetes mellitus can be divided into 2 parts: acute complications and chronic complications. That can will also affect the functional status of patients. Functional status is a person's ability in carrying out everyday activities in a healthy manner. This study aims to determine the relationship betwen the complications of diabetes mellitus with patient's functional status, with  a cross sectional design. Sample consisted of 48 people selected by purposive sampling technique. The data was collected by  using the short form 12 questionnaire and filled out by respondents. Based on statistical tests product moment strength of the relationship obtained for 77.8%. Based on the above findings suggested that nurses can provide comprehensive nursing care to prevent complications of diabetes mellitus and to retain and improve the functional status of patients.